Students’ Interest and Cognitive Ability through the Implementation of Comic Media - Sisean Baga; Mila Ermila Hendriyani; Suratmi Suratmi; Maria Magdalena Rosaline (Gemilang Maju Publikasi Ilmiah (GMPI), 2021)
This study aimed to determine the students' interest and cognitive ability through the implementation of comic media on the environmental pollution concept at one of Junior High School in Serang City, Indonesia. The method used in this study is a descriptive research. The subject in this study was class VII.2. The class was chosen because of the information from the subject teacher that it has students who are less active in learning and obtained the lowest average score of all class VII in the first semester. The data collection technique used non-test instruments in observation sheets and questionnaires to determine the students' interest. The test instrument was in multiple-choice questions and open-ended essay to determine the students' cognitive ability. The results showed students' interest as measured by observation and questionnaires were in the high category with 56% and 88%, respectively. The average value of the students' cognitive ability is 65.59, with a good category. It can be concluded that the implementation of comic media can foster students' interest in learning. The results of this study can be a suggestion for curriculum developers to use comics as an alternative media for an exciting learning process. Future studies can focus more on specific comic components that can attract students' attention in the learning process.